Soil animal microhabitat temperatures in Svalbard (High Arctic) and on the Antarctic peninusula - Coulson, Stephen; Sjöblom, Anna; Convey, Peter (University3, 2019)
Annual temperature data from microhabitats inhabited by soil invertebrates at diverse locations in Svalbard (European High Arctic) and on the Antarctic peninsula. This data are recorded at hour intervals and span several years providing detailed temperature information during all four seasons. Temperatures were recorded in the microhabitat, a depth of c. 5 to 10mm. They can be used to understand the actual temperatures encountered by soil organisms and how these microhabitat temperatures differ from the air temperatures recorded by meteorological stations or active layer temperatures determined by permafrost stations.
They are intented to be used as example data and are particularly useful for sites where year round monitoring is not possible.

Arctic
Temperatures were recorded at a depth of approximately 1 cm using Tinytag dataloggers, TGP-4020 (Gemini, Chichester, West Sussex, U.K.) fitted with PB-5001, PB-5009, or PB-5006 external thermistor probes, except for the Small temporary and Large permanent ponds (sites O and P) where
TG-4100 submersible loggers were deployed at approximately 10 cm water depth. For logger and probe locations see Online Resource 1. Care was taken to avoid exposing the sensors to direct insolation. Sampling interval was 30, 60 or 120 min, depending on logger memory and expected campaign period.

Antarctic
Ground and air temperatures were recorded using various temperature probes over time (copper/constantan thermocouple wires; type-T thermocouples; Fenwal Unicurve thermistors UUT51J1 (100 KΩ at 25 °C) in type FF catheter probes; HMP45C, Vaisala; Campbell Scientific 107 thermistor probes, Campbell Scientific, UK). For ground temperatures
the probe was inserted into the ground surface so as to record surface conditions. Air temperatures were recorded at a height of 2 m within a naturally ventilated solar insolation shield. Data were recorded every hour for the duration of the study using Campbell Scientific CR10X loggers (Campbell Scientific, U.K.).

Data sources:
Svalbard. S. J. Coulson, University Centre in Svalbard (UNIS), pb 156, 9171 Longyearbyen, Svalbard, Norway.
Antarctic. P. Convey and M.R. Worland, British Antarctic Survey, High Cross, Madingley Road, Cambridge, CB3 0ET, United Kingdom.

Årliga temperaturdata från små biotoper som bebos av ryggradslösa djur på diverse platser i Svalbard (Europeiska högarktis) och på den Antarktiska halvön presenteras. Data som visas är temperaturen varje timma och sträcker sig över flera år. Temperaturer registrerades i mikrohabitat på ett djup av ca 5-10 mm. Datat kan användas för att förstå de faktiska temperaturerna i mikrohabitater och hur dessa skiljer sig från lufttemperaturen som registreras av meteorologiska stationer och temperaturer mätt i det aktiva lagret vid permafroststationer. Data är avsett att användas som exempeldata och är särskilt användbara för platser där det inte är möjligt med åretrunt övervakning.

Arktiska temperaturer registrerades på ett djup av ca 0,5 till 1 cm med Tinytag dataloggrar, TGP-4020 (Gemini, Chichester, West Sussex, U.K.) försedda med PB-5001, PB-5009 eller PB-5006 externa termistor sonder, med undantag för små tillfälliga och stora permanenta dammar (platser O och P) där TG-4100 dataloggrarna distribuerades på cirka 10 cm vattendjup. Se Online resurs 1 för en komplett beskrivning. Provtagningsintervall var 30, 60 eller 120 min, beroende på loggerns minne och den förväntade mätperioden. I Antarktis registrerades mark och luft temperaturerna med olika sonder (koppar/Konstantan termoelement ledningar; typ-T termoelement; Fenwal Unicurve termistorer UUT51J1 (100 KΩ vid 25 ° C) i typ FF katetern sonder; HMP45C, Vaisala; Campbell Scientific 107 termistor sonder, vetenskapliga Campbell, UK). För mätning av marktemperaturen infogades sonden i markytan. Lufttemperaturer registrerades på en höjd av 2 m inom en naturligt ventilerad solinstrålningssköld. Data registrerades varje timme under hela försöket med Campbell vetenskapliga CR10X loggers (Campbell Scientific, U.K.).

Data sources:
Svalbard. S. J. Coulson, University Centre in Svalbard (UNIS), pb 156, 9171 Longyearbyen, Svalbard, Norway.
Antarctic. P. Convey and M.R. Worland, British Antarctic Survey, High Cross, Madingley Road, Cambridge, CB3 0ET, United Kingdom.
Temperaturer i ryggradslösa djurs mikrohabitat på Svalbard (Arktis) och på Antarktiska halvön
Keywords: ARCTIC TUNDRA; ANIMALS/INVERTEBRATES; Antarctica; Antarktis; Arctic region; Bio-geographical regions; Biogeografiska regioner; Habitats and biotopes; Naturtyper och biotoper; Meteorological geographical features; Geografiska meteorologiska förhållanden; Species distribution; Arters utbredning; microhabitats; mikrohabitat; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Biota; Biologi och ekologi; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi